Pengaruh Permainan Monopoli Card Terhadap Kemampuan Motorik Kasar Anak Usia 5-6 Tahun - Rabihatun Adawiyah; Rohyana Fitriani; Zuhut Ramdani; Eva Mupira Hardian (Jurnal Golden Age, 2022)
This study aims to see the effect of monopoly card media on gross motor skills of children aged 5-6 years. The research method used in this study is an experimental method with a Pre-Experimental Design type with a One Group Pretest Posttest design. The data collection technique used is observation. The results of the pretest observation were 57% (BB), and 82% posttest (BSB). From the results of the calculation of the normality test data, it shows that the data from the pretest observations are69,866 > 23,685 count> tablethe data is normally distributed, and the results of the t-test for the observation data arepretest results (13), posttest results (26) yielded (13.6) t=1.07Thus, it is stated that there is an effectiveness of gross motor development of children aged 5-6 years before and after using the monopoly card game media or tools.